Recovery from hemorrhoids and anal fissure without surgery - Abdullah Şişik; Fatih Başak; Mustafa Hasbahçeci; Aylin Acar; Ali Kılıç; Yahya Özel; Gürhan Baş (Turkish Journal of Gastroenterology, 2020)
Background/Aims: An anal fissure (AF) is a linear tear in the distal anal canal and is one of the most common causes of anal pain. Hemorrhoidal disease (HD) is a symptomatic growth and distal displacement of normal anal cushions. Numerous studies have addressed the contributing factors of these conditions, yet the results remain controversial. In this study, we hypothesize that increasing patients’ awareness of hidden risk factors could reduce the rate of HD and AF. Materials and Methods: A questionnaire-based controlled study was planned. After power analysis, patients with HD (n=60) and AF (n=60) were enrolled consecutively into the study group and compared with the control group (n=60) of healthy individuals. The survey was designed to assess the participants’ toilet and dietary habits and anxiety risk. Odds ratios were calculated and a binary logistic regression model was constructed to identify associated factors. Results: Hard stools, spending more than 5 minutes in the toilet, frequent straining during defecation, and increased spice intake were more frequent in the patients with HD; and hard fecal consistency, time elapsed in toilet greater than 5 min, straining during defecation, and high anxiety risk were more frequent in the patients with AF as compared to the control group (p<0.05). Conclusion: Possible associations were identified between habitual factors or conditions (i.e., fecal consistency, the time elapsed in the toilet, straining during defecation) and anxiety and benign anorectal diseases (i.e., HD and AF). Patients should be advised about these hidden threats. Cite this article as: Şişik A, Başak F, Hasbahçeci M, et al. Recovery from hemorrhoids and anal fissure without surgery. Turk J Gastroenterol 2020; 31(4): 289-94.